Energy and Protein Requirements in Pre-Starter Diets of Broiler Chicks during the First Week Posthatch (Journal of Hama University, 2019)
An experiment was carried out using 300 unsexed chicks of a commercial broiler breed taken randomly from a hatchery after the start of hatching. The chicks were distributed into six groups of 50 chicks each. The chicks were fed a certain type of mash feed for 7 days as follows:The chicks of the1st  group were given the basal Pre-Starter diet directly after hatching having 3000k.cal/kg Metabolisable Energy (ME), and 23% Crude Protein (CP).While the 2nd group of chicks  were given the Pre-Starter diet directly after hatching but having ME=3000k.cal/kg, CP=25%.The 3rd and the 4th  group of chicks  were given the Pre-Starter diet directly after hatching but having  (ME=3100k.cal/kg, CP=23%),(ME=3100k.cal/kg, CP=25%) respectively.The 5th  group of chicks  were given the Pre-Starter diet directly after hatching but having  ME=3200k.cal/kg, CP=23% This diet is conformed to the American feed tables (NRC, 1994). While the 6th  group of chicks  were given the Pre-Starter diet directly after hatching but having ME=3200k.cal/kg, CP=25%. and maintaining the rest of the nutrients as in the basal diet.  After 7 days the chicks of six groups fed a broiler pellet commercial diet until the age of 42 days.The results showed the importance of the Sixth group (ME=3200k.cal/kg, CP=25%) in the diet directly after hatching on the average live weight at the end of the first week, the differences were significant (P ≤ 0.01), (P ≤ 0.05) between the chicks of the Sixth group compared to rest of the groups except the fifth group.No significant differences were noticed among the average live weight of the chicks of all groups at the end of the experiment.It was showed that the Sixth group in the diet directly after hatching improved feed conversion ratio (1.68) compared to birds of  the another  groups at the end of the experiment.